+0  
 
0
102
1
avatar

b1+b2=-5 5b1+2b2=-12 b1=,b2=

Guest May 6, 2017

Best Answer 

 #1
avatar+4172 
+5

I think these are the equations:

b1 + b2 = -5

5b1 + 2b2 = -12

 

Solve the first equation for b1 by subtracting b2 from both sides.

b1 = -5 - b2

 

Substitute this value for b1 into the second equation.

5(-5 - b2) + 2b2 = -12

 

Distribute and combine like terms.

-25 - 5b2 + 2b2 = -12

-25 - 3b2 = -12

 

Add 25 to both sides of the equation.

-3b2 = -12 + 25

-3b2 = 13

 

Divide both sides by 7.

b2 = -13/3

 

Substitute this value for b2 into either of the given equations to find b1.

b1 + -13/3 = -5

b1 = -5 + 13/3

b1 = -2/3

hectictar  May 7, 2017
Sort: 

1+0 Answers

 #1
avatar+4172 
+5
Best Answer

I think these are the equations:

b1 + b2 = -5

5b1 + 2b2 = -12

 

Solve the first equation for b1 by subtracting b2 from both sides.

b1 = -5 - b2

 

Substitute this value for b1 into the second equation.

5(-5 - b2) + 2b2 = -12

 

Distribute and combine like terms.

-25 - 5b2 + 2b2 = -12

-25 - 3b2 = -12

 

Add 25 to both sides of the equation.

-3b2 = -12 + 25

-3b2 = 13

 

Divide both sides by 7.

b2 = -13/3

 

Substitute this value for b2 into either of the given equations to find b1.

b1 + -13/3 = -5

b1 = -5 + 13/3

b1 = -2/3

hectictar  May 7, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details